If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+(x-5)=1
We move all terms to the left:
2x+(x-5)-(1)=0
We get rid of parentheses
2x+x-5-1=0
We add all the numbers together, and all the variables
3x-6=0
We move all terms containing x to the left, all other terms to the right
3x=6
x=6/3
x=2
| (y+8)(y+29)=0 | | -5x-2=-x+18 | | 7v+15=4v+33 | | 2x+x-5=1 | | 18.2+2y=6y+7 | | 2+(3x+1)=5x+7 | | 4w+1=8w+17 | | 4/6x-3/6=2/6+5/6x | | 3×(x-6)=2×(x-7) | | 3u+20=7u-12 | | z÷3=2 | | 2x-2+3x-3=18 | | 964=n+34 | | 2x+15=25-4x | | t/24=27 | | t÷24=27 | | 2×(x+1)=2x+10 | | 4(b+3)+2b=3(b-11) | | 17c=935 | | 289=y+464 | | t+55=68 | | q+46=95 | | 4×(x-5)=-12 | | -4y=928 | | 219=w+-650 | | 36=r+30 | | q-7.67=20.34 | | 5.08/12.5=x | | -10x-4+3x=10 | | 9=33-4f | | -11+3(b+5)=22 | | +4x-8=+12 |